Meet Addy : an American girl - Connie Porter; Taylor, Dahl (Middleton, Wis. : Pleasant Co., 1864)
In 1864, after her father and brother are sold to another owner, nine-year-old Addy Walker and her mother escape from their cruel life as slaves in North Carolina to freedom in Philadelphia.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Slavery -- Fiction; Underground Railroad -- Fiction